A study on short term outcome of stroke in a rural tertiary care center of Sub Himalayan Terai - Saha, Sanchita; Ghosh, Susmita; Chakraborty, Sisir; Ghosh, Kaushik; Acharyya, Amitava; Kundu, Piyali; Sherpa, Pasang Lahmu; Biswas, Atanu (Asian Journal of Medical Sciences, 2018)
Background: Stroke is the second most common cause of mortality in the world, causing immense morbidity and economic burden. The proper knowledge of the factors which influence the good clinical outcome in stroke is utmost strength of the clinicians in India, where post stroke rehabilitative measures are limited. Aims and Objective: To find out the association of outcome of stroke with different risk factors. Materials and Methods: A descriptive observational design study was formulated for a period of six months on hundred stroke patients in internal medicine unit of at North Bengal Medical College & Hospital, India. Patients were selected after proper screening by inclusion and exclusion criteria. The “In-hospital-outcome” of CVA patient was determined by Glasgow outcome scale. The neurological condition was determined by National Institute of Health Stroke Scale (NIHSS). The Modified Rankin Scale and Barthel Index were utilized to asses disability status of patient in different period of hospital admission. The data were analyzed by EPI INFO software. Results: Clinical outcome showed statistically significant (P<0.05) correlation with age, sex, level of consciousness, blood pressure, diabetes, past history, mass effect, size and depth of infarction and intra-ventricular extension of intra cerebral bleeding. Other parameters like type of stroke (ischemic or hemorrhagic), delay in admission, dyslipidemia, presence of heart disease, smoking, alcoholism, family history, depth and volume of intra cerebral bleeding, although showed poorer clinical outcome, their correlation was not statistically significant. Conclusion: In-hospital outcome of stroke as determined by Glasgow outcome scale correlates with diverse clinical parameters including various risk factors. Asian Journal of Medical Sciences Vol.9(4) 2018 1-9